NBS1 promotes the endonuclease activity of the MRE11‐RAD50 complex by sensing CtIP phosphorylation. (20th February 2019) - Anand, Roopesh; Jasrotia, Arti; Bundschuh, Diana; Howard, Sean Michael; Ranjha, Lepakshi; Stucki, Manuel; Cejka, Petr
Abstract: DNA end resection initiates DNA double‐strand break repair by homologous recombination. MRE11‐RAD50‐NBS1 and phosphorylated CtIP perform the first resection step via MRE11‐catalyzed endonucleolytic DNA cleavage. Human NBS1, more than its homologue Xrs2 in Saccharomyces cerevisiae, is crucial for this process, highlighting complex mechanisms that regulate the MRE11 nuclease in higher eukaryotes. Using a reconstituted system, we show here that NBS1, through its FHA and BRCT domains, functions as a sensor of CtIP phosphorylation. NBS1 then activates the MRE11‐RAD50 nuclease through direct physical interactions with MRE11. In the absence of NBS1, MRE11‐RAD50 exhibits a weaker nuclease activity, which requires CtIP but not strictly its phosphorylation. This identifies at least two mechanisms by which CtIP augments MRE11: a phosphorylation‐dependent mode through NBS1 and a phosphorylation‐independent mode without NBS1. In support, we show that limited DNA end resection occurs in vivo in the absence of the FHA and BRCT domains of NBS1. Collectively, our data suggest that NBS1 restricts the MRE11‐RAD50 nuclease to S‐G2 phase when CtIP is extensively phosphorylated. This defines mechanisms that regulate the MRE11 nuclease in DNA metabolism. Synopsis: The crucial contribution of NBS1, the accessory subunit in the mammalian MRN complex, for initiating end resection of DNA double‐strand breaks is defined by in vitro reconstitution to lie in sensing of CDK‐dependent CtIP phosphorylation, providing a link to cell cycle stage. NBS1 senses CtIP phosphorylation via its FHA and BRCT domains. NBS1 stimulates the MRE11‐RAD50 nuclease by directly interacting with MRE11. NBS1 restricts the nuclease of MRE11‐RAD50 to conditions when CtIP is phosphorylated. In absence of NBS1, phosphorylation of CtIP is not strictly required to promote the nuclease of MRE11‐RAD50. Abstract : In vitro reconstitution defines the crucial contribution of the accessory subunit in the mammalian MRN complex for end resection of DNA double‐strand breaks.